Virtual Reality Immersive Simulations for a Forensic Molecular Biology Course-A Quantitative Comparative Study - Ewais, Ahmed; Mystakidis, Stylianos; Khalilia, Walid; Diab, Shadi; Christopoulos, Athanasios; Khasib, Said; Yahya, Baha; Hatzilygeroudis, Ioannis (MDPI, 2025)
Molecular biology is a complex, abstract, subject that can be challenging for higher education students to comprehend. The current manuscript describes the design, implementation, and evaluation of two immersive VR simulations of a DNA lab and a crime scene investigation (CSI) for a forensic molecular biology course in the context of the "TESLA" Erasmus+ project. It illustrates the instructional design and technical aspects of the VR simulations' development. The experimental study employed a comparative quantitative research design. The guiding research questions examined how instructional modalities (online vs. face-to-face) affect learners' perceptions of VR-based training in higher education and the key factors influencing learners' intention for their adoption. Forty-six (n = 46) undergraduate students completed a 17-item questionnaire, which served as the main data collection instrument. Results demonstrate that both online and face-to-face VR-based instruction can effectively convey core concepts, thus challenging the traditional notion that face-to-face interaction is inherently superior. Its implications underscore the potential of VR simulations to supplement or even substitute traditional teaching methods, particularly for complex science subjects.